2016
DOI: 10.3892/etm.2016.3850
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of geraniol inhibits inflammatory response, oxidative stress and apoptosis in traumatic injury of the spinal cord through modulation of NF-κB and p38 MAPK

Abstract: Abstract. Geraniol is a type of monoterpenoid with a rose scent and a slightly sweet flavor. It is found in the volatile oil of various plants, and has anti-inflammatory and anti-oxidant effects. The present study aimed to investigate the protective effect of geraniol in inhibiting the inflammatory response, oxidative stress and apoptosis in traumatic spinal cord injury (SCI), as well as to analyze the mechanism underlying its effect. Adult male Sprague-Dawley rats were induced to traumatic SCI through a surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 31 publications
(37 reference statements)
3
36
0
Order By: Relevance
“…This includes their ability to reduce the levels of or the formation of ROS and RNS, concomitantly upregulating vitagenes, such as members of the heat shock protein (Hsp) family, heme oxygenase-1, and Hsp70 [8,26]. GE has been reported as an effective antioxidant and antiinflammatory agent in different experimental models from our lab and others [16][17][18][19]21,29]. Recently, the antioxidant activity of GE along with other actives has been published with respect to DPPH free radical scavenging activity and superoxide dismutase activity [30].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This includes their ability to reduce the levels of or the formation of ROS and RNS, concomitantly upregulating vitagenes, such as members of the heat shock protein (Hsp) family, heme oxygenase-1, and Hsp70 [8,26]. GE has been reported as an effective antioxidant and antiinflammatory agent in different experimental models from our lab and others [16][17][18][19]21,29]. Recently, the antioxidant activity of GE along with other actives has been published with respect to DPPH free radical scavenging activity and superoxide dismutase activity [30].…”
Section: Discussionmentioning
confidence: 93%
“…It is also found in a wide range of cleansing products and cosmetics for its appealing odor [13,14]. In the recent past, several studies have recognized the pharmacological potential of GE in different models [15][16][17]. Its pharmacological property is by virtue of its antioxidant and anti-inflammatory properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…GOH, a special type of acyclic monoterpene alcohol, has been widely used to treat many diseases related to inflammation, including dextran sulfate sodium (DSS)-induced colitis in mice [ 28 ]. Moreover, GOH has been shown to inhibit cell apoptosis in traumatic spinal cord injury (SCI) [ 29 ]. In our study, a mouse model of ALI was successfully established by the intranasal administration of LPS, and we investigated the anti-inflammatory and anti-apoptotic effects of GOH on LPS-induced ALI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Fas/FasL and Bcl-2 genes are two of the key factors influencing apoptosis and regulating the intrinsic apoptosis pathway in renal tubular epithelial cells ( 18 , 19 ). In addition, the intrinsic apoptosis pathway is activated by oxidative stress, which is mediated by increased mitochondrial membrane permeability ( 20 ). Previous studies have suggested that oxidative stress is involved in the apoptotic mechanism mediated by the Fas/FasL signaling pathway ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%